2008
DOI: 10.17221/375-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of housing system on the calcium requirement of laying hens and on eggshell quality

Abstract: The effects of housing systems on the calcium requirement for eggshell production, eggshell quality and on the breaking strength of the hen’s tibia were evaluated. Unenriched cages (UN) (24 laying hens), enriched cages (EN) (16 laying hens) and floor system (FS) (24 laying hens) were used in this experiment. The eggshell production of laying hens from 19 to 66 weeks of age was higher (<I>P</I> < 0.01) in the cage systems (UN 39.6 g/hen/week and EN 39.2 g/hen/week) than it was in FS (35.0 g/hen/w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
20
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 21 publications
(18 reference statements)
5
20
0
1
Order By: Relevance
“…These results disagree with those of van den Brand et al (2004), who recorded greater eggshell thickness and strength in eggs from outdoor layers. However, Lichovníková and Zeman (2008) reported higher eggshell strength in eggs from cages. Also Hidalgo et al (2008) showed the effect of housing on eggshell thickness and strength.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…These results disagree with those of van den Brand et al (2004), who recorded greater eggshell thickness and strength in eggs from outdoor layers. However, Lichovníková and Zeman (2008) reported higher eggshell strength in eggs from cages. Also Hidalgo et al (2008) showed the effect of housing on eggshell thickness and strength.…”
Section: Discussionmentioning
confidence: 91%
“…The rates of calcium deposition in shells of eggs produced in the two systems are possibly different. Lichovníková and Zeman (2008) showed that calcium content in the shell and calcium intake were higher in cages than on litter. Structural differences in the eggshell formation according to a housing system may be the result of variable pore density in eggs from cages and litter.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The utilisation of calcium is irregularly decreased in the laying cycle period by the age of hens. Lichovníková and Zeman (2008) presented the ratio of calcium in the eggshell to calcium intake (%) 47.6% in the cages to 38.7% on deep litter at the beginning of the laying cycle period and 44.2% to 38.9% at the end of the laying cycle period. In our experiment the calcium utilisation was found to be lower (30.65% in the 1 st cycle and 29.09% in the 2 nd cycle in the first experiment and 31.62; 29.91 and 20.45% in the 1 st , 2 nd and 3 rd cycle in the second experiment).…”
Section: Discussionmentioning
confidence: 99%
“…In the experiment (Lichovníková and Zeman, 2008) the rate of calcium intake deposited in the eggshells was higher in cage systems compared with a floor system depending on the age of laying hens. Řezáč et al (2000) recorded that the plasma calcium level was higher in hens with cracked eggshells than in hens with unbroken eggshells but this difference was not significant.…”
mentioning
confidence: 87%